Integration of sports and initial mathematical concepts in the preparatory group during activities on the basketball court - Živanović, Milan V.; Marković, Miloslav B. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2025)
The modern model of preschool education and upbringing "Years of Ascent” requires a holistic approach to working with children, which, among other things, methodologically implies an interactive approach to content, and organizationally a project-based method of work imbued with play and other work methods accessible to children. This paper will describe the situations of learning of length measurement and concepts of meter and centimeter in the preparatory preschool group on the elements of the basketball game and the field. This achieves the integration of initial mathematical concepts and physical education. The activities can be implemented through a wider multi-day project "Sports and Mathematics".
Keywords: length measurement; meter; centimeter; integration; preparatory group